Exosomes from Human Umbilical Cord Mesenchymal Stem Cells Reduce Damage from Oxidative Stress and the Epithelial-Mesenchymal Transition in Renal Epithelial Cells Exposed to Oxalate and Calcium Oxalate Monohydrate - Dian Li; Dan Zhang; Bo Tang; Yue Zhou; Wenhao Guo; Qing Kang; Zhang Wang; Lianju Shen; Guanghui Wei; Dawei He (Stem Cells International)
Objective. To investigate whether exosomes from human umbilical cord mesenchymal stem cells (hUC-MSCs) can protect against the toxic effects of oxalate and calcium oxalate monohydrate (COM) crystals in human proximal tubular epithelial (HK-2) cells. Methods. Exosomes were isolated from hUC-MSCs, purified by ultracentrifugation, and verified by examination of cell morphology using transmission electron microscopy and the presence of specific biomarkers. HK-2 cells received 1 of 4 treatments: control (cells alone), hUC-MSC exosomes, oxalate+COM, or oxalate+COM and hUC-MSC exosomes. Cell viability was determined using the MTT assay. Oxidative stress was determined by measuring LDH activity and the levels of H2O2, malondialdehyde (MDA), and reactive oxygen species (ROS). Expressions of N-cadherin, TGF-β, and ZO-1 were determined by immunofluorescence. Expressions of epithelial markers, mesenchymal markers, and related signaling pathway proteins were determined by western blotting. Results. After 48 h, cells in the oxalate+COM group lost their adhesion, appeared long, spindle-shaped, and scattered, and the number of cells had significantly decreased. The oxalate+COM treatment also upregulated TGF-β and mesenchymal markers, downregulated epithelial markers, increased the levels of LDH, H2O2, MDA, and ROS, decreased cell viability, and increased cell migration. The isolated exosomes had double-layer membranes, had hollow, circular, or elliptical shapes, had diameters mostly between 30 and 100 nm, and expressed CD9, CD63, and Alix. Treatment of HK-2 cells with hUC-MSC exosomes reversed or partly reversed all the effects of oxalate+COM. Conclusions. Exosomes from hUC-MSCs alleviate the oxidative injury and the epithelial-mesenchymal transformation of HK-2 cells that is induced by oxalate+COM.